Answer:
[tex]f(x)=-\left(\dfrac{1}{2}\right)^x+4[/tex]
The exponential function is increasing and is concave down
Step-by-step explanation:
Let the equation of exponential function be
[tex]f(x)=a\cdot b^x+c,\ ,\ b>0[/tex]
1. Exponential function f(x) has a y intercept of 3, so the graph of f(x) passes through the point (0,3). Thus,
[tex]3=a\cdot b^0+c\\ \\3=a+c[/tex]
2. Exponential function f(x) has an x intercept of -2, so the graph of f(x) passes through the point (-2,0). Thus,
[tex]0=a\cdot b^{-2}+c\\ \\0=\dfrac{a}{b^2}+c[/tex]
3. Function is always increasing as the value of x increases, but the function never reaches y=4, so
[tex]c=4[/tex]
Hence,
[tex]\left\{\begin{array}{l}a+4=3\\ \\\dfrac{a}{b^2}+4=0\end{array}\right.\Rightarrow \left\{\begin{array}{l}a=-1\\ \\\dfrac{-1}{b^2}+4=0\end{array}\right.\Rightarrow \left\{\begin{array}{l}a=-1\\ \\b^2=\dfrac{1}{4}\end{array}\right.[/tex]
So,
[tex]a=-1,\\ \\b=\dfrac{1}{2},\\ \\c=4,\\ \\f(x)=-\left(\dfrac{1}{2}\right)^x+4[/tex]